PENENTUAN POTENSI KEDALAMAN DAN KANDUNGAN BIJIH BESI DI DESA AJUNG KABUPATEN BALANGAN KALIMANTAN SELATAN - Dewi, Raisa Kusuma; Wianto, Totok; Wahyono, Sri Cahyo (Lambung Mangkurat University Press, 2013)
ABSTRACT: Ajung Village District of Balangan, astronomically are located 114º 5031 115 ° 5024 E and 2 º 131 - 2 ° 3558 S. Based on the geologicalmap, the Ajung Village District Balangan is Haruyan formation, Ultramafic Rocksand Granodiorit. The erosion of Ultramafic rocks, especially serpentinit undergochemical decomposition and accumulation of iron ore. Since the potential of ironore in Ajung Village is not certain then in this study the authors conducted astudy to determine the potential depth and content of iron ore by using 3Dgeoelectric Dipole Dipole configuration, Atomic Absorption Spectrophotometer(AAS) and X-ray flourescence (XRF). The results of field measurements 3Dgeoelectric method Dipole Dipole configurations with the potential depth of ± 0to 2.05 meters in the form of chunks of rock with prices between 1594 -2442Ohm.meter resistivity. The average Fe content of elements in the iron ore fromAjung village, District Balangan by laboratory analysis using AAS was 50.01%,while 94.82% are using XRF.Keywords: iron ore, geoelectric, AAS, XRF